Philosophical Perspective of Islamic Economics - Fatmawati Sungkawaningrum (Yayasan Rumah Peneleh, 2022)
This paper aims to investigate philosophical perspective of Islamic economics since it is believed that religion is a provision from God to humans to live in the order of religious values. Through literature studies, the study concludes that human's nature is good and continuously attempting to purify or tazkiyah him/herself. This purification process that is termed in Islam as as hifdzun al aql or tazkiyatun nafs, will place an element of peace, including in the development of knowledge in the study of economics.